ANALISIS GAYA BELAJAR DALAM PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN BAHASA INDONESIA DI SD NEGERI SENDANGMULYO 02 - Agung Tri Wibowo; Duwi Nuvitalia; Husni Wakhyudin (STKIP Subang, 2023)
Various student learning styles make student learning styles a preferred habit during the learning process. This study aims to analyze the learning styles of class IVA students in the differentiated learning program at SDN Sendangmulyo 02 Semarang. This study uses a qualitative descriptive research method. Data collection techniques used are observation, interviews, and questionnaires given to students to obtain accurate data. The results reveal that teachers can better cope with the diversity of learning styles by gaining a deep understanding of their students' learning styles and adapting their teaching strategies accordingly. This study shows that among the 28 students of SD Negeri Sendangmulyo 02 Semarang studied, 54% showed a visual learning style, 29% had an auditory learning style, and 18% had a kinesthetic learning style. Differentiated learning was found to be an effective approach to accommodate these varied learning styles.